Diet-induced obesity exacerbates metabolic and behavioral effects of polycystic ovary syndrome in a rodent model - Ressler, Ilana B. (Am J Physiol Endocrinol Metab, 2015)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy affecting women of reproductive age. Although a comorbidity of PCOS is obesity, many are lean. We hypothesized that increased saturated fat consumption and obesity would exacerbate metabolic and stress indices in a rodent model of PCOS. Female rats were implanted with the nonaromatizable androgen dihydrotestosterone (DHT) or placebo pellets prior to puberty. Half of each group was maintained ad libitum on either a high-fat diet (HFD; 40% butter fat calories) or nutrient-matched low-fat diet (LFD). Irrespective of diet, DHT-treated animals gained more body weight, had irregular cycles, and were glucose intolerant compared with controls on both diets. HFD/DHT animals had the highest levels of fat mass and insulin resistance. DHT animals demonstrated increased anxiety-related behavior in the elevated plus maze by decreased distance traveled and time in the open arms. HFD consumption increased immobility during the forced-swim test. DHT treatment suppressed diurnal corticosterone measurements in both diet groups. In parallel, DHT treatment significantly dampened stress responsivity to a mild stressor. Brains of DHT animals showed attenuated c-Fos activation in the ventromedial hypothalamus and arcuate nucleus; irrespective of DHT-treatment, however, all HFD animals had elevated hypothalamic paraventricular nucleus c-Fos activation. Whereas hyperandrogenism drives overall body weight gain, glucose intolerance, anxiety behaviors, and stress responsivity, HFD consumption exacerbates the effect of androgens on adiposity, insulin resistance, and depressive behaviors.